أثر تقلبات تجارة الغاز الطبيعي على الاقتصاد الجزائري في ظل جائحة كورونا خلال الفترة (1990-2020) - وسام, قماري; وئام, حمية; زهرة, حفيظي (University of eloued جامعة الوادي, 2022)
يحتل الغاز الطبيعي مكانة هامة في الاقتصاد الجزائري لأنه يعتبر ركيزة أساسية لمداخيل وموازنة الدولة، وبالتالي حدوث أي تغيرات مفاجئة أو أزمات غير متوقعة في سوق العالمي للغاز الطبيعي قد يؤدي بالوضع الاقتصادي لهاوية الانكماش والركود. هدفت هذه الدارسة إلى توضيح وقياس مدى تأثير تقلبات تجارة الغاز الطبيعي على الاقتصاد الجزائري تزامنا مع ظهور أزمة كورونا وتدهور أسعار النفط والغاز وذلك بإستخدام نموذج الانحدار الذاتي للفجوات الزمنية الموزعة ARDL خلال الفترة (1990-2020). وقد توصلت الدراسة إلى وجود علاقة طردية طويلة الأجل بين صادرات الغاز الطبيعي expo والناتج المحلي الاجمالي GDP في ظل وجود وباء كورونا "The natural gas is occupying an important place in the economy of Algeria because it is a fundamental pillar of the revenues and the state budget, it follows any changes sudden occurrence or unexpected crises in the global market for natural gas could lead to the economic situation of the abyss of deflation and recession, this study aimed to clarify and measure the impact of fluctuations in trade natural gas on the Algerian economy to coincide with the appearance of Corona virus crisis and the deterioration of the price of oil and gas using a form of self regression of the gaps of time distributed ARDL during the period (1990- 2020) the study found a long term positive relationship between natural gas exports (EXPO) and gross domestic product (GDP) With the presence of Corona epidemic."
ماستر اقتصاد
Keywords: الغاز الطبيعي، فيروس كورونا، الناتج المحلي الاجمالي، صادرات الغاز الطبيعي; The gaz natural, Corona virus, gross domestic product,natural gaz exports